Digital Architects: Providing Solutions for Long Term Development - Alexandra-Maria DANILET (Communications of International Proceedings, 2021)
Technology and innovation have become two concepts that are indispensable in the processes of implementing the development strategies of decision-makers, both at the microeconomic and macroeconomic levels. The growing interest in these topics also arises from the intense global competition in the race to conquer new markets, but also from the need to identify new ways of coping with changes in both society and the environment. From this perspective, business organizations aiming at long-term development, maintaining or improving of their market position have to reconfigure the way they carry out their activities and organizational processes either by incorporating technologies/innovations or by creating/developing new methods/techniques/processes, i.e. by promoting and supporting their own innovative activity. From this perspective, ICT companies are becoming key players in a society where digitalization has become a necessity, an aspect also highlighted by the global pandemic triggered by COVID-19. Whether we are talking about different hardware equipment/devices or other hardware components, or different software, applications, software platforms or different types of software, we can state with certainty that these are essential, we would say critical, elements in the digital infrastructure of a successful company that aims to be competitive. Therefore, developing a technology information infrastructure represent a key issue in the strategy regarding the future progress and the digital architects, namely the companies in the technology domain have an increasing role in proving the necessary technology means.
Keywords: Technology; Development; Innovation; Strategy; Digitalization.